Importance of human breast milk in premature infant - Simonetta Costa; Francesca Serrao; Chiara Tirone; Eloisa Tiberi; Mirta Corsello; Francesca Priolo; Milena Tana; Francesca Paola Fusco; Simonetta Frezza; Giovanni Vento (Nutrimentum et Curae, 2022)
Human breast milk (HBM) is considered the optimum feeding for infant nutrition. The specific composition and unique properties make HBM appropriate not only for the term but also for preterm infants. HBM feeding confers protection to preterm infants against the most serious morbidities of prematurity and decreases mortality in a dose-dependent manner. We performed a literature review, aiming to provide an update on the available evidence regarding the importance and the advantages of HBM on preterm infants’ health. Our findings confirmed the several health benefits in preterm infants, including the improvement of neurodevelopmental outcomes and the protection against necrotizing enterocolitis and infections. Many more investigations will be necessary to understand the mechanisms underlying the beneficial association of HBM with neurodevelopmental outcomes and to confirm the beneficial effects of HBM on bronchopulmonary dysplasia. Based on the current evidence on the health benefit of HBM feeding, promotion and support of lactation since the immediate post-delivery should be considered a priority in preterm infants’ care.